On the Approach of the 10th Anniversary of the Signing of the “Grand Treaty” on the Creation of the EAEU: New Challenges and New Opportunities - Balasanyan, Grigor (YSU Journal of International Affairs, 2023)
Everyone knows that integration processes are, first of all, an opportunity that must be used to achieve good results. In the modern era of globalization, the degree of interaction between states in all spheres of life is increasing. In the context of the transition to a multipolar world, regional unions play an important role. In 2024 marks the 10th anniversary of the signing of the so-called "Great Treaty", which was of great importance for the formation of the EAEU. Moreover, the Union was formed precisely based on this treaty. As for the multi-vector integration processes in the post-Soviet space, the key event for these processes was the creation of the Eurasian Economic Union. In turn, Eurasian integration is a geopolitical project in response to the expansion of the European Union (EU) zone. The Eurasian Union initiative was initially ambitious. its goal was to create a supranational union like the EU. We can say that the creation of the Eurasian Union is the cornerstone of the history of integration processes in the post-Soviet space. Initially, the Union was created as an economic association, the purpose of which was the development of the economy and economic relations between the member countries of the Union. This is especially important for small economies such as Armenia and Kyrgyzstan. For Armenia, we can say that the republic's export opportunities to the EAEU countries have grown almost 10 times.
Keywords: Treaty; EAEU; EU; integration processes; barriers; international cooperation